Belarus and NATO in the 1990-th: History of Relations, Fundamental Problems and Progress Trends - O K Petrovich-Belkin (Vestnik RUDN. International Relations, 2011)
The article is devoted to the history and analysis of relations between the Republic of Belarus and NATO in the 1990th. It focuses on fundamental problems and principal progress trends in their relationship.